An image encryption algorithm with a plaintext‐related quantisation scheme. Issue 9 (18th March 2021) - Oravec, Jakub; Ovseník, Ľuboš; Papaj, Ján
Abstract: This paper describes an image encryption algorithm that utilises a plaintext‐related quantisation scheme. Various plaintext‐related approaches from other algorithms are presented and their properties are briefly discussed. Main advantage of the proposed solution is the achievement of a similar behaviour like that of more complex approaches with a plaintext‐related technique used in a rather simple step such as quantisation. This design should result in a favourable computational complexity of the whole algorithm. The properties of the proposal are evaluated by a number of commonly used numerical parameters. Also, the statistical properties of a pseudo‐random sequence that is quantised according to the plain image pixel intensities are investigated by tests from NIST 800‐22 suite. Obtained results are compared to values reported in related works and they imply that the proposed solution produces encrypted images with comparable statistical properties but authors' design is faster and more efficient.